Estimativa da evaporação potencial, em condições de campo, usando o tanque «classe A» modificado - da Silva, Wilson Jesus; C Sediyama, Gilberto; T Coelho, Dirceu; Bernardo, Salassier (Revista Ceres, 2025)
Screened Class A evaporation pans were employed for estimating upward ‘water vapor flux from bodies of water. The measured values of evaporation data ‘were compared to standart Class A evaporation pan data and the estimated value of evapotranspiration by the methods of Penman, Bowen and McIlroy.